From Scheme to System (Part 2): Findings from Ten Countries on the Policy Evolution of Results-Based Financing in Health Systems. Issue 2 (3rd April 2017) - Shroff, Zubin Cyrus; Bigdeli, Maryam; Meessen, Bruno
Abstract: Abstract — This article presents the enablers and barriers to the scaling-up of results-based financing (RBF) programs. It draws on the Alliance for Health Policy and Systems Research's multicountry program of research Taking Results Based Financing From Scheme to System, which compared the scale-up of RBF interventions over four phases—generation, adoption, institutionalization, and expansion—across ten countries. Comparing country experiences reveals broad lessons on scale up of RBF for each of the scale-up phases. Though the coming together of global, national, and regional contextual factors was key to the development of pilot projects, national factors were important to scale up these pilots to national programs, including a political context favoring results and transparency, the presence of enabling policies and institutions, and the presence of policy entrepreneurs at the national level. The third transition, from program to policy, was enabled by the availability of domestic financial resources, legislative and financing arrangements to enhance health facility autonomy, and technical and political leadership within and beyond the Ministry of Health. The article provides lessons learned on RBF policy evolution, emphasizing the importance of phase-specific groups of actors, the need to tailor advocacy messages to enable scale-up, the influence of political feasibility on policy content, and policy processes to build national ownership and enable health system strengthening.